PENGARUH PENGETAHUAN KEWIRAUSAHAAN, E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGAMBILAN KEPUTUSAN MAHASISWA AKUNTANSI UNTUK BERWIRAUSAHA DIMASA PANDEMI (STUDI KASUS MAHASISWA AKUNTANSI UNIVERSITAS ISLAM MALANG) - Agustin Nilamsari; Maslichah Maslichah; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2022)
This research aims to find out how the influence of entrepreneurial knowledge, e-commerce, and accounting information systems on entrepreneurial decisions during the pandemic. The independent variables in this research are entrepreneurial knowledge, e-commerce, and accounting information systems. While the dependent variable is the entrepreneurial decision. This research is a correlational quantitative research. The data that used in this research is primary data with data collection methods in the form of a questionnaire technique. The population in this research is undergraduate students of the accounting study program, Faculty of Economics and Business, Islamic University of Malang batch 2018 and 2019. The data collection technique used purposive sampling which refers to the Slovin formula. In this research, the data that could be processed were 83 respondents. The data analysis technique used multiple linear regression analysis. The results of this study indicate that: 1) Knowledge of entrepreneurship, e-commerce and accounting information systems have a simultaneous effect on student entrepreneurship decisions during the pandemic. 2) Knowledge of entrepreneurship has a significant positive effect on student entrepreneurship decisions during the pandemic. 3) E-commerce has a significant positive effect on student entrepreneurship decisions during the pandemic. 4) The accounting information system has a significant positive effect on student entrepreneurship decisions during the pandemic.Keywords: entrepreneurial knowledge, e-commerce, accounting information systems, and entrepreneurship decisions.